Jazz and blues - Brasch, Nicolas. frey50 (North Mankato, Minn. : Smart Apple Media, 2005)
Presents the history, instruments, performers, and compositions of jazz and blues music.
Includes index.
"A+."
First published: South Yarra, Vic. : Macmillan Education Australia, 2003.
Keywords: Jazz -- History and criticism -- Juvenile literature; Blues (Music) -- History and criticism -- Juvenile literature; Jazz; Blues (Music)